Importance of N2BA titin in maintaining cardiac homeostasis and its role in dilated cardiomyopathy - van der Pijl, Robbert; Nusayr, Eyad; Strom, Joshua; Slater, Rebecca; Gohlke, Jochen; Hourani, Zaynab; Saripalli, Chandra; Kolb, Justin; Hermanson, Kyra; Brynnel, Odhin; Smith, John E.; Labeit, Siegfried; et al. (Circulation. Heart failure, 2025)
BACKGROUND: - TTN (titin) is the third myofilament type of the cardiac sarcomere and performs important functions that include generating passive tension. Changes in TTN expression are associated with cardiac dysfunction, and TTN is one of the main genes linked to dilated cardiomyopathy (DCM). DCM is frequently associated with changes in the expression of N2BA (compliant cardiac TTN isoform), 1 of the 2 major TTN isoforms found in the heart (the other isoform being the N2B [stiff cardiac TTN isoform]). Whether altered expression of N2BA TTN causes DCM or is a secondary change remains unclear. - METHODS: - Here, we present a mouse model, the TtnΔ112-158 model, which specifically shortens the proline, glutamate, valine, lysine region of the N2BA isoform. - RESULTS: - Echocardiography and pressure-volume analysis revealed a DCM phenotype characterized by systolic dysfunction and dilation. RNA sequencing studies showed the absence of proline, glutamate, valine, lysine exons, as expected, but also reduced expressions of exons specific to the N2BA isoform of TTN. Protein studies revealed a reduction in the overall expression level of the N2BA isoform with a concomitant increase in N2B TTN, with preserved TT (total TTN) levels. Passive tension was modestly increased in the TtnΔ112-158 model. Western blotting revealed that the N2BA TTN-associated protein MARP1 (muscle ankyrin repeat protein 1) is downregulated during both the pre-DCM and DCM phase. Downregulation of MARP1 coincided with the downregulation of the transcription factor Gata-4 (GATA binding protein 4), an MARP1-regulating and interacting protein, which is associated with DCM development. - CONCLUSIONS: - Thus, N2BA TTN is essential for maintaining cardiac health, and perturbed N2BA-MARP1 signaling contributes to DCM development.
Online veröffentlicht: 11. Februar 2025
Gesehen am 17.06.2025